ANALISIS NILAI-NILAI KEWIRAUSAHAAN DALAM FILM UPIN IPIN UNTUK PEMBELAJARAN DI SEKOLAH DASAR - Pramesti, Diana; Dewani, Ratih Surya; Arafatun, Sasih Karnita (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2024)
This research was motivated by the importance of entrepreneurial values among elementary school children through the film Upin Ipin, which can be applied in daily life by making habits from both the family and school environment. The purpose of this study was to determine the value of entrepreneurship in the film Upin Ipin. This study used descriptive qualitative as an approach. The subject of this research was the film Upin Ipin. Data collection techniques in this study used observation. Meanwhile, the data analysis technique used the Miles and Huberman model with 3 stages, namely data reduction, data display, and conclusion drawing/verification. The findings show that the entrepreneurial values found in the film of Upin Ipin which derived from the episodes of